Access to Market Financing for IDA-eligible Countries-the Role of External Debt and IMF-Supported Programs - Thomas, Alun (IMF Working Papers; Working Paper ;, 2009)
Exclusion restrictions used to identify demand and supply relationships for market financing among IDA recipients (past and present) show that poor credit ratings and high political instability adversely impact the supply of market finance. While the adverse effects of external debt on market access occur at very high levels for IDA-eligible countries, the sizeable debt relief provided in the context of the enhanced HIPC Initiative has significantly raised the likelihood of market access for these countries. For countries that have graduated from IDA financing, the length of country spells in IMF-supported programs raises the likelihood of market access, although this effect is absent for IDA-eligible countries.